Emotional Intelligence in Elementary School Children. EMOCINE, a Novel Assessment Test Based on the Interpretation of Cinema Scenes - Sastre, Santiago; Artola, Teresa; Alvarado, Jesús M. (Frontiers in Psychology, 2019)
The aim of the present study was to validate a new procedure, called EMOCINE test, to measure the perception and understanding branches of emotional intelligence (EI) in 1,448 children, aged between 8 and 13 years, from elementary schools. This new tool consists of watching 15 cartoon film clips and interpreting them according to children’s own emotional perception and comprehension. After completing the test, the participants were classifie, according to their responses and by using the latent class analysis, as naïve (16.1%), over-interpretative (33.5%), and sensitive (50.4%). An increase in sensitive responses was observed depending on participants sex (girls higher than boys), and academic grade (increasing over the grades). Participants from the sensitive latent class had a significant better behavior in the school/classroom, compared with those from naïve and over-interpretative groups. Likewise, significant differences between latent classes were observed in many psychological, emotional, and behavioral problems (mainly between sensitive vs. insensitive by naivety) such as: depression, post-traumatic symptomatology, attention problems, aggression, family problems, problems at school, problems with classmates, integration and social competence. In conclusion, EMOCINE is a novel and promising tool for the measurement of the perception and comprehension components of EI. The test, employing film clips, is more realistic and motivating than others using static images or written descriptions. Moreover, the test can predict or identify emotional and behavior problems in children.